Short Communication Resistance Against African Stem Rust (Puccinia graminis tritict) Race Ug99 in Advanced Wheat Lines and Varieties Developed by Public Breeding Programmes in NWFP, Pakistan - Shah, Syed Jawad Ahmad; Mobmmad U, Tila; Hussain, Shaukat; lbrahim, M.; Khan, Waseemullah; Ali, Sajid (Biological Sciences - PJSIR, 2007)
Stem rust is a n i mportant d isease of w heat wor l dw ide. Under t h e CTMMYT/ I CARDA facilitated testin g at Kenya, 1 05 l i nes/ variet i es from Pakista n were screened agai n st novel stem rust race Ug99 durin g 2006 . All entri es were found vul n erable to Ug99. North West Frontier Province (N WFP) of Pakistan is u nder poten t i al threat from t hi s stem r ust race and wheat material from the region al so di sp layed clear cu t susceptibi l ity except var. Sul cman-96 and Dera-98 which demon strated M -MSS type reaction . Resistance of th ese genotypes can be enhanced if effect i ve stem rust resista nce genes are i ncorpo rated in the i r background s becau se both are local l y adopted varieties in NWFP.